Case study - AMAZON - Bader Althafairi; Noura Alhoumaida; Muskan Saxena; Zahraa Almsri (AIBPM Publisher, 2019)
Amazon is the first large company that sells goods and services over the internet it was founded by jeff bezos in 1994. Amazon started out as an online book store then it grows quickly to add new items such as DVD’s, video games, electronics, clothing and more to the extent that the company logo symbolizes means that they sell all products from A to Z. Amazon.com try their best to get customer loyalty and trust. They offer state shipping service and they have many retail stores in different countries. It also purchases customer data and information to achieve customer needs and wants. Amazon is one of the first in the world to sell online and has many competitors like: ebay, rakuten and flipkart. Therefore, amazon has own over 40 subsidiaries includes: zappos, shopbop, IMDb, Amazon Prime, appstore, and amazon drive.